Rheological, mechanical and tribological properties of carbon-nanofibre reinforced poly (ether ether ketone) composites - Altstaedt,Volker (2003)
Poly(ether ether ketone) nanocomposites containing vapour-grown carbon nanofibres (CNF) were produced using standard polymer processing techniques. At high shear rates no significant increase in resin viscosity was observed. Nevertheless, the addition of the CNFs results in a higher melt strength at 360°C. Electron microscopy confirmed the homogeneous dispersion and alignment of nanofibres in the polymer matrix. Evaluation of the mechanical composite properties revealed a linear increase in tensile stiffness and strength with nanofibre loading fractions up to 15 wt% whilst matrix ductility was maintained up to 10 wt%. An interpretation of the composite performance by short-fibre theory resulted in rather low intrinsic stiffness properties of the vapour-grown CNF. Differential scanning calorimetry was used to investigate crystallization kinetics and degree of crystallinity. The CNFs were found not to act as nucleating sites. Furthermore, unidirectional sliding tests against two different counterpart materials (100Cr6 martensitic bearing steel, X5CrNi18-10 austenitic stainless steel) were performed. The carbon nanofibres were found to reduce the wear rate of PEEK significantly.